Anxiety Disorders at Outpatient Psychiatric Services: Clinical Presentations and Associated Features (Community Based Medical Journal, 2025)
A cross-sectional, descriptive study was conducted in the outpatient psychiatry department of Community Based Medical College, Bangladesh (CBMC,B), Mymensingh, Bangladesh, between June and December of 2024, to assess the clinical presentations and associated factors of anxiety disorders among outpatients attending the hospital. A total of 68 participants selected through purposive sampling, those who were previously diagnosed with anxiety disorders according to DSM-5 criteria. Data on sociodemographic characteristics, clinical symptoms, and associated factors were collected through interviews and medical records. Generalized Anxiety Disorder-7 (GAD-7)  scale was used for assessment. Analysis was performed using MS Office tools (Excel and Word). The study found generalized anxiety disorder as most prevalent (47.1%), with excessive worriedness (85.3%), restlessness (73.5%), and somatic complaints (61.8%) as key symptoms. Females (64.7%) and low-income individuals (52.9%) were disproportionately affected. Comorbidities were observed in 38.2% patients with mostly suffering from hypertension (20.6%). Financial stress (32.4%) was also a significant contributor. GAD-7 scores revealed 69.1% had moderate to severe levels of anxiety, while 38.2% had severe form of disease and 14.75 had mild anxiety. This study highlights a significant burden of anxiety disorders among our population particularly among women and those belong to the low-income group. The high prevalence of somatic symptoms and comorbidities underscores the need for integrated care approaches addressing both psychological and physical health in our resource-limited settings.  CBMJ 2025 July: vol. 14 no. 02 P:9-14